Determinants of firms’ access to finance through fintech: An empirical study of startup firms in Vietnam - Pham, Ngoc Anh; Nguyen, Quyen Do; Nguyen, Dzung Viet (Asian Economic and Financial Review, 2025)
This study examines the determinants influencing Vietnamese startup firms' access to finance through Fintech platforms. Drawing on survey data and employing the Heckman two-stage estimation procedure, this research investigates how internal firm characteristics, such as R&D investment intensity, capital sources, industry classification, and revenue growth, affect the likelihood of securing Fintech-based funding. The results reveal that firms with prior capital access, high R&D-to-revenue ratios, and recent capital-raising activity are more inclined to access Fintech finance. Conversely, startups that rely predominantly on government support or external equity tend to have lower engagement with Fintech solutions. Moreover, sectoral variation exists, with specific industries displaying greater compatibility with Fintech models due to differing capital needs and innovation profiles. The study contributes to the growing literature on entrepreneurial finance and Fintech by providing empirical evidence from an emerging market context. It also offers policy implications to enhance financial inclusion and support innovation, emphasizing the need for legal frameworks to foster Fintech development, targeted support for R&D-driven startups, and stronger collaboration between Fintechs and traditional financial institutions. By identifying key enablers and constraints of Fintech adoption, this research provides practical insights for startups, policymakers, and investors seeking to navigate Vietnam’s evolving financial landscape.